Pengaruh Herbisida Metil Metsulfuron dan Kombinasinya pada Pengendalian Gulma Tanaman Tebu (Saccharum officinarum L.) - Muhammad Aziz Setiawan; Sismita Sari; Mirodi Syofian (Jurnal Agroteknologi, 2021)
Weed control must use the right dose of herbicide so as not to leave a residual effect on cultivated plants and soil. This study ains to obtain the most appropriate dose of herbicide. Herbicide used in this study were methyl methulfuron and acetic acid combined. This study used a randomized block design (RCBD) witch 2 factors, factor A was asetic acid and factor B was methyl methulfuron and there were 12 treatment combinations with 3 replications. This research was conducted in the practicum of the Departement of Plantation Plant Cultivation, Lampung State Polytechnic. The total research plot was 36 experimentals units. The dosage levels levels of methyl methulfuron tested in this study were: 0%, 55%, 75%, and 105%. While the dose of acetic acid is: 0%, 50%, and 70%. Observations made in this study were weed vegetation analysis, weed cover percent, weed dry weight, Summed Dominance Ratio (SDR), and Community Coefficient Value (C). SDR values indicate that Panicum dicotomyflorum weed, Ricardia brasiliensis, Euphorbia heterophyla, and Cyperus rotundus are the dominant weeds. The results of this study indicate that there is no effect on the dose of methyl methulfuron herbicide, acetic acid, and interactions on methyl methulfuron herbicide and acetic acid on weed control in sugarcane fields (Saccharum officinarum L.).